EVALUASI PELAKSANAAN KIS (KARTU INDONESIA SEHAT) DI DESA PINTU GOBANG KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Maybella Anggraini; Syapril Abdullah (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This research aim to know Evaluation of KIS Implementation (Healthy indonesian card) In Pintu Gobang Kari Village Kuantan Tengah Sub-district Kuantan Singingi Regency. This research method is Descriptive Survey. The study is located in the village door gobang curry. The population in this research is 26 people. Sampling technique done by Purposive Sampling Technique is determination of sample with certain consideration. In this study the authors set as many as 26 people. The results showed that the Evaluation of the Implementation of KIS (Healthy indonesian card) In Pintu Gobang Kari Village Kuantan Tengah Sub-district Kuantan Singingi Regency in Less Less Exacted category. Concerning the effectiveness of community respondents as recipients of KIS card (Healthy indonesian card) card in Less Appropriate category. Efficiency of community respondent as receiver of KIS card (Healthy indonesian card) card in Less Appropriate category. The sufficiency of the community respondents as the recipients of the KIS card (Healthy indonesian card) card in the Less Implemented category. The similarity of the community respondents as the recipients of the KIS card (Healthy Indonesia Card) card in the Less Implemented category. Responsiveness of community respondents as beneficiaries of KIS card (Healthy indonesian card) in the Self-Implemented category. The accuracy of the community respondents as the recipients of the KIS card card (Healthy indonesian card) in the Less Implemented category. This conclusion is in accordance with the measurement technique that has been determined that the Less Understandable category is in the percentage of 26% - 50% meaning that 6 indicators used are not all done well.